Penggeseran Aspek Hukum Publik ke Aspek Hukum Privat (Bantuan Likuiditas Bank Indonesia) - Aang Achmad (Fakultas Hukum Universitas Islam Indonesia, 2011)
This research discusses the issues of obstacles in the settlement of Bank of Indonesia Liquidity Support criminal conduct. This research is a doctrinal or juridical normative research. The legal materials are collected through literary study and documentary study. The materials are then qualitatively analyzed. Through these methods, the research concludes that the delay of the settlement of Bank of Indonesia Liquidity Support criminal conduct caused by: (1) the system of criminal law that has formal-legalisticpositivistic character; (2) complex proof; (3) the absence of cooperation with states where the assets located; and (4) the not yet applied reverse proof.Key words : Corruption, Bank of Indonesia Liquidity Support, Private Law